Kinetic, thermodynamic, and mechanistic patterns for free (unbound) cytochrome c at Au/SAM junctions: Impact of electronic coupling, hydrostatic pressure, and stabilizing/denaturing additives - Seyferth, Stefan; et al. (Chemistry - A European Journal, 2006)
Combined kinetic (electrochemical) and thermodynamic (calorimetric) investigations were performed for an unbound (intact native-like) cytochrome c (CytC) freely diffusing to and from gold electrodes modified by hydroxyl-terminated self-assembled monolayer films (SAMs), under a unique broad range of experimental conditions. Our approach included: 1) fine-tuning of the charge-transfer (CT) distance by using the extended set of Au-deposited hydroxyl-terminated alkanethiol SAMs [-S-(CH)-OH] of variable thickness (n = 2, 3, 4, 6, 11); 2) application of a high-pressure (up to 150MPa) kinetic strategy toward the representative Au/SAM/CytC assemblies (n = 3, 4, 6); 3) complementary electrochemical and microcalorimetric studies on the impact of some stabilizing and denaturing additives. We report for the first time a mechanistic changeover detected for "free" CytC by three independent kinetic methods, manifested through 1) the abrupt change in the dependence of the shape of the electron exchange standard rate constant (k ) versus the SAM thickness (resulting in a variation of estimated actual CT range within ca. 15 to 25 Å including ca. 11 Å of an "effective" heme-to-ω-hydroxyl distance). The corresponding values of the electronic coupling matrix element vary within the range from ca. 3 to 0.02cm ; 2) the change in activation volume from +6.7 (n = 3), to ≈ 0 (n=4), and -5.5 (n=6) cmmol (disclosing at n=3 a direct pressure effect on the protein's internal viscosity); 3) a "full" Kramerstype viscosity dependence for k at n = 2 and 3 (demonstrating control of an intraglobular friction through the external dynamic properties), and its gradual transformation to the viscosity independent (nonadiabatic) regime at n=6 and 11. Multilateral cross-testing of "free", CytC in a native-like, glucose-stabilized and urea-destabilized (molten-globule-like) states revealed novel intrinsic links between local/ global structural and functional characteristics. Importantly, our results on the high-pressure and solution-viscosity effects, together with matching literature data, strongly support the concept of "dynamic slaving", which implies that fluctuations involving "small" solution components control the proteins' intrinsic dynamics and function in a highly cooperative manner as far as CT processes under adiabatic conditions are concerned. © 2006 Wiley-VCH Verlag GmbH & Co. KGaA.